2020
DOI: 10.1002/solr.202000241
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Nonfullerene Organic Solar Cells Enabled by Atomic Layer Deposited Zirconium‐Doped Zinc Oxide

Abstract: Organic solar cells (OSCs) are promising photovoltaic devices and zinc oxide (ZnO) is a commonly used electron transport layer (ETL) in OSCs. However, the conventional spin-coating ZnO layer is currently limiting its efficiency potential. Herein, it is shown for the first time that atomic layer deposition (ALD), which allows for controlled thin film growth with atomic-scale control, can effectively be used to optimize the ZnO for nonfullerene OSCs. First, density functional theory (DFT) calculations are discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 97 publications
(116 reference statements)
0
16
0
Order By: Relevance
“…The chemical structures of the PTB7-Th polymer donor and PC 70 BM fullerene acceptor with the energy level alignment of the devices are illustrated in Figure 1 . The semiconductor band edge energy positions and the metal work functions were provided from refs ( 15 ), ( 20 ), ( 28 ), and ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical structures of the PTB7-Th polymer donor and PC 70 BM fullerene acceptor with the energy level alignment of the devices are illustrated in Figure 1 . The semiconductor band edge energy positions and the metal work functions were provided from refs ( 15 ), ( 20 ), ( 28 ), and ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…The acceptor alloy Y6:BTP-M in combination with donor PM6 delivered an outstanding PCE of 17.03 %. Figure 7f, g shows the energy level diagram and chemical structures of PM6, Y6 and BTP-M. Another derivative of Y6, N3, was studied in a PM6:N3-based solar cell by Poduval et al [124] In comparison to ZnO ETL, the device with Zr-doped ZnO ETL showed an increased PCE reaching 14.7 % in the inverted device structure.…”
Section: Fttb-pdi4mentioning
confidence: 99%
“…and Zhang et al. doped ZnO with zirconium (Zr), which improved the optoelectronic properties and sufficiently lowered the defect density, thus improving the device performances of the related NF‐OSCs [18f,g] . Yu et al.…”
Section: Electron Transporting Materialsmentioning
confidence: 99%